2021
DOI: 10.1002/jha2.312
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of ciltacabtagene autoleucel in CARTITUDE‐1 versus physician's choice of therapy in the Flatiron Health multiple myeloma cohort registry for the treatment of patients with relapsed or refractory multiple myeloma

Abstract: Introduction Ciltacabtagene autoleucel (cilta‐cel) is a novel chimeric antigen receptor T‐cell therapy that is being evaluated in the CARTITUDE‐1 trial (NCT03548207) in patients with relapsed or refractory multiple myeloma (RRMM) who received as part of their previous therapy an immunomodulatory drug, proteasome inhibitor, and an anti‐CD38 monoclonal antibody (i.e., triple‐class exposed). Given the absence of a control arm in CARTITUDE‐1, this study assessed the comparative effectiveness of cilta‐cel and physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…TTNT was defined as the time between the index date and initiation of the next treatment or death, whichever occurred first. If none of these criteria were met, patients were censored at the last visit date or the study end date [11] , [16] . OS was defined as the time from the index date to date of death.…”
Section: Methodsmentioning
confidence: 99%
“…TTNT was defined as the time between the index date and initiation of the next treatment or death, whichever occurred first. If none of these criteria were met, patients were censored at the last visit date or the study end date [11] , [16] . OS was defined as the time from the index date to date of death.…”
Section: Methodsmentioning
confidence: 99%
“…These results provide compelling evidence regarding the benefits of cilta-cel for the treatment of TCE RRMM patients and align with other recent analyses involving externally derived controls for CARTITUDE-1 from different countries, despite variability in the RWCP regimens. 9–14 The current study demonstrated important gains with cilta-cel compared to RWCP for ORR, ≥VGPR, PFS, TTNT, and OS. Patients treated with cilta-cel are 3.0 and 11.5 times more likely to reach ORR and ≥VGPR, respectively, and had substantial improvements in PFS (by 88%), TTNT (by 89%), and OS (by 87%).…”
mentioning
confidence: 64%
“…We retrieved 3133 unique records, of which 200 were included in the review (Figure 1). All reasons for excluding records after full-text review are given in eAppendix 6 in Supplement 1.…”
Section: Resultsmentioning
confidence: 99%
“…One-hundred and fifteen studies (58%) completely reported how the target trial protocol was emulated. Eighty-seven studies (44%) provided both the protocol of the target trial and described how it was emulated (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation